2012
DOI: 10.1038/srep00208
|View full text |Cite
|
Sign up to set email alerts
|

Zscan4 transiently reactivates early embryonic genes during the generation of induced pluripotent stem cells

Abstract: The generation of induced pluripotent stem cells (iPSCs) by the forced expression of defined transcription factors in somatic cells holds great promise for the future of regenerative medicine. However, the initial reprogramming mechanism is still poorly understood. Here we show that Zscan4, expressed transiently in 2-cell embryos and embryonic stem cells (ESCs), efficiently produces iPSCs from mouse embryo fibroblasts when coexpressed with Klf4, Oct4, and Sox2. Interestingly, the forced expression of Zscan4 is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
91
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(104 citation statements)
references
References 46 publications
(82 reference statements)
12
91
1
Order By: Relevance
“…We found that Zscan4f strongly enhanced reprogramming efficiency in combination with OSK or OSKM ( Figure 1B), while the other two factors did not enhance iPS cell formation. This is consistent with a recent independent study, which also showed the enhancement of reprogramming efficiency by Zscan4 [27].…”
Section: Zscan4 Dramatically Decreases Ddr During Reprogramming and Esupporting
confidence: 82%
See 1 more Smart Citation
“…We found that Zscan4f strongly enhanced reprogramming efficiency in combination with OSK or OSKM ( Figure 1B), while the other two factors did not enhance iPS cell formation. This is consistent with a recent independent study, which also showed the enhancement of reprogramming efficiency by Zscan4 [27].…”
Section: Zscan4 Dramatically Decreases Ddr During Reprogramming and Esupporting
confidence: 82%
“…In our study, we identified Zscan4 as a factor, essential for cleavage development of mouse embryos [23], which not only remarkably promotes the efficiency of iPS cell generation, but also significantly improves the quality of iPS cells by stabilizing the genomic and telomere DNA and promoting the telomere elongation at early stage of reprogramming. Consistently, a recent independent study [27] also verified that Zscan4 can improve the reprogramming efficiency.…”
Section: Discussionsupporting
confidence: 62%
“…Zscan4 promotes the efficiency and quality of iPSC generation, although it is only transiently activated for the initial few days during the early reprogramming process [32,33]. This finding strongly suggests that activation of Zscan4 may improve the quality of iPSCs during early reprogramming and long-term culture.…”
Section: Introductionmentioning
confidence: 84%
“…Considering the beneficial effects of Zscan4 gene expression in previous studies [31,32,35], we examined whether the small molecules enhance Zscan4 expression and preserve the genomic stability of iPSCs during reprogramming. Zscan4 promotes telomere elongation without activation of telomerase [33] and plays important roles in the maintenance of genomic stability in ESCs and iPSCs [31,33].…”
Section: Small Molecules Promote Expression Of the Zscan4 Gene Duringmentioning
confidence: 99%
“…Approximately 45% (173 out of 383) of the transcripts also showed up-regulation during the 1C-to-2C transition; as 150 of these were expressed in sperm, this again suggested that the majority were sperm-primed nascent transcripts. These genes included Spz1, Smad7, and the Oocyte 1C 2C 4C MEF p1C p4C miscRNA 4128 5242 6184 6547 8428 4259 6196 asRNA 236 273 269 245 310 233 215 snoRNA 152 148 159 167 164 153 160 Pseudo 142 143 140 135 108 127 134 miRNA 18 19 40 46 112 15 46 snRNA 10 10 10 12 11 9 8 Total 4686 5835 6802 7152 9133 4796 6759 potential pluripotency regulators Pramel1, Pramel6, and Pramel7 (Wang et al 2001;Casanova et al 2011;Hirata et al 2012). We also identified a dramatic change in expression during the 1C-to-2C transition, in which 4967 and 4082 transcripts were down-regulated and up-regulated, respectively, at 2C relative to 1C.…”
Section: Analysis Of Differential Gene Expressionmentioning
confidence: 99%